Accidents in relation to the environmental design hazards in residential interior spaces - Racca, Kathrina Kate B.; Faustino, Johanna Victoria Acab. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT Despite the safety provisions in design, little is known about the occurrence of accidents in the homes. Injury and death incidences caused by home accidents call for more attention to look at safety as a significant factor of design. This study probed the causes of accidents and injuries in twenty residential houses. Non-probability sampling procedures using snowball purposive sampling design was used to select respondents in this study. The study was limited to twenty single detached houses in Metro Manila and Rizal with records of accidents and injuries sustained by the respondents. Data were gathered through interview schedules and observation. The interview questionnaire was composed of 10 open-ended questions incorporated with dichotomous questions. The study determined the kinds of injuries sustained by the respondents and identified the areas where accidents usually occur in the house. As an explanatory research, this study determined the relationship between the occurrence of home accidents and the quality of the physical environment of the residential interior spaces. The interior of the residential houses were assessed to determine the environmental design hazards that contributed to accidents and injuries. Although human factors are involved in the occurrence of accidents, it was found that the environmental design hazards present in the accident-prone areas caused and heightened the probability of accidents and injuries. Common environmental hazards that were found in the study were due to violations in design standards, the use of inappropriate materials, and faulty design execution. Hence, this study calls for interior designers' attention to ensure that their design is followed in the actual construction.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Home accidents -- Environmental design aspects